2020
DOI: 10.51260/revista_espamciencia.v11i1.209
|View full text |Cite
|
Sign up to set email alerts
|

Importancia de la producción de la concha prieta (Anadara tuberculosa) en las costas ecuatorianas

Abstract: La extracción de la concha prieta (Anadara tuberculosa) es una actividad productiva ancestral, que se realiza de manera espontánea e intuitiva y cuya importancia no ha sido suficientemente ponderada, destacada y reconocida en los diversos ámbitos gubernamentales, empresariales y académicos del Ecuador y de otros países que también la producen. Esta investigación tiene por objetivo indagar sobre los indicadores que determinan la importancia económica, social y ambiental a nivel global y nacional de la producció… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…In the economic productivity subdimension, it was evidenced that the participants in the CP production chain have always experienced moderate improvements in their income (35.4%). In comparison, 23.1% experienced that their income has rarely increased [15]. However, the monthly revenue per shell collector was estimated between 427 and 640 USD, a range below the basic family basket in Ecuador, 712.11 USD, equivalent to a 40% to 10% deficit.…”
Section: Source: Authorsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the economic productivity subdimension, it was evidenced that the participants in the CP production chain have always experienced moderate improvements in their income (35.4%). In comparison, 23.1% experienced that their income has rarely increased [15]. However, the monthly revenue per shell collector was estimated between 427 and 640 USD, a range below the basic family basket in Ecuador, 712.11 USD, equivalent to a 40% to 10% deficit.…”
Section: Source: Authorsmentioning
confidence: 94%
“…The productivity dimension was integrated by the indicators of the physical productivity subdimension and economic productivity. The productivity dimension investigated whether production was sufficient to satisfy customer demands, as Prado-Carpio et al [15] indicated. In the economic productivity subdimension, it was evidenced that the participants in the CP production chain have always experienced moderate improvements in their income (35.4%).…”
Section: Source: Authorsmentioning
confidence: 99%
“…La metodología consistió en una exploración y análisis de publicaciones relacionada con el tema, con énfasis en la producción académica generada a partir de la investigación doctoral de Prado-Carpio (2020), Prado-Carpio et al 2019;2020a;2020b;2020c). Una vez procesada la información de manera integral, analizados los antecedentes obtenidos de la estudio bibliográfico, los resultados obtenidos y la experiencia de los investigadores, se priorizaron las estrategias más importantes para esta cadena de suministro con base al desempeño reportado (Prado-Carpio, 2020;Prado-Carpio et al, 2020c).…”
Section: Materiales Y Métodosunclassified
“…The productivity dimension was integrated by the indicators of the physical productivity subdimension and economic productivity. The productivity dimension investigated whether production was sufficient to satisfy customer demands, as Prado-Carpio et al [10,28] indicated. In the economic productivity subdimension, it was evidenced that the participants in the A. tuberculosa production chain have always experienced moderate improvements in their income (35.4%).…”
Section: Performance Of the Anadara Tuberculosa Supply Chainmentioning
confidence: 99%